2016
DOI: 10.1111/jan.13003
|View full text |Cite
|
Sign up to set email alerts
|

A randomized controlled trial of an educational programme with telephone reinforcement to improve perceived health status of Brazilian burn victims at 6‐month post discharge

Abstract: The educational programme, when compared with usual care, reduced anxiety symptoms and post-traumatic stress. Educational programmes with telephone follow-up might be a viable intervention to improve self-care for burn victims.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 59 publications
1
9
0
1
Order By: Relevance
“…Findings from this study showed that there was a significantly positive effect of the programme on selfmanagement; this results was similar to those of studies that exam- Although positive change trends in the outcomes were observed in this study, there were no significant differences between the two groups in the dimensions of self-management, haemodialysis knowledge and self-efficacy. This finding was similar to those in another study (Goncalves, Ciol, Dantas, Farina Junior, & Rossi, 2016) where burn patients participated in an educational programme with telephone reinforcement; that study also showed no significant difference in self-management between the intervention and control groups. The non-significant findings in this study may be explained by the following.…”
Section: Discussionsupporting
confidence: 90%
“…Findings from this study showed that there was a significantly positive effect of the programme on selfmanagement; this results was similar to those of studies that exam- Although positive change trends in the outcomes were observed in this study, there were no significant differences between the two groups in the dimensions of self-management, haemodialysis knowledge and self-efficacy. This finding was similar to those in another study (Goncalves, Ciol, Dantas, Farina Junior, & Rossi, 2016) where burn patients participated in an educational programme with telephone reinforcement; that study also showed no significant difference in self-management between the intervention and control groups. The non-significant findings in this study may be explained by the following.…”
Section: Discussionsupporting
confidence: 90%
“…Mean scores per domain were assessed and high scores refer to a good perceived health status. Of the 47 studies that used the BSHS-B or BSHS-R, 17 could be used to analyze HRQL recovery patterns [ 19 , 26 , 38 , 40 , 49 , 60 , 64 , 67 , 76 , 81 83 , 88 , 90 , 91 , 102 , 105 ] ( S1 Fig ).…”
Section: Resultsmentioning
confidence: 99%
“…Four of the six studies found a significant improvement in knowledge: (1) cardiac self‐efficacy ( p < .01, Cajanding et al, 2017); (2) heart failure knowledge ( p < .001, Davis et al., 2012),; (3) understanding of congenital heart disease (CHD) risk factors, diet, medication, physical exercise ( p < .001, Zhao & Wong, 2009); and (4) self‐perceived risk and knowledge about falls ( p < .001, Hill et al., 2013). Two of the six studies found a non‐significant difference in: (1) stroke knowledge (Hoffman et al, 2015); and (2) perceived self‐efficacy ( p = .53, Goncalves et al, 2016).…”
Section: Resultsmentioning
confidence: 99%